Identification of microorganisms by mass spectrometry (John Wiley, 2006)
Identification of Microorganisms by Mass Spectrometry represents the most comprehensive and up-to-date work on the topic currently available. It is liberally illustrated with figures and tables and covers every aspect of spectrometric identification of microorganisms, including experimental procedures, various means of sample preparation, data analysis, and interpretation of complex mass spectral data.